2002
DOI: 10.1128/iai.70.12.7126-7135.2002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Requirements for Salmonella -Induced Cytopathology in Human Monocyte-Derived Macrophages

Abstract: Infection of human macrophages with Salmonella enterica serovar Typhimurium or Salmonella enterica serovar Dublin produces delayed cytotoxicity characterized by cell detachment and associated apoptosis. Using a site-specific mutant in the SpvB active site, we verify that the ADP-ribosylation activity of SpvB is required for delayed cytotoxicity in human macrophages infected with Salmonella. SipB and the type III protein secretion system (TTSS) encoded by Salmonella pathogenicity island 1 (SPI1) are not involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 43 publications
2
85
0
Order By: Relevance
“…One report showed that SpvB could be secreted into a culture medium mimicking the intracellular iron concentrations of eukaryotic cells in a T3SS-independent manner [316]. However, several components of the T3SS2, have been shown to be essential for SpvB-induced actin depolymerization and delayed cytotoxicity, strongly supporting the idea that SpvB is translocated into the host cell through T3SS2 [314,317].…”
Section: Spvb and Spvcmentioning
confidence: 98%
See 1 more Smart Citation
“…One report showed that SpvB could be secreted into a culture medium mimicking the intracellular iron concentrations of eukaryotic cells in a T3SS-independent manner [316]. However, several components of the T3SS2, have been shown to be essential for SpvB-induced actin depolymerization and delayed cytotoxicity, strongly supporting the idea that SpvB is translocated into the host cell through T3SS2 [314,317].…”
Section: Spvb and Spvcmentioning
confidence: 98%
“…SpvB inhibits the formation of vacuole-associated actin polymerizations (VAPs) in HeLa cells [312] and negatively regulates the formation of SIFs [313]. The ADP-ribosylation activity of SpvB is also required for a delayed form of cell death that is observed in host cells 18-24 h after infection with noninvasive bacteria or T3SS1 mutants [67,85,314,315]. One report showed that SpvB could be secreted into a culture medium mimicking the intracellular iron concentrations of eukaryotic cells in a T3SS-independent manner [316].…”
Section: Spvb and Spvcmentioning
confidence: 99%
“…Browne and coworkers demonstrated earlier that the infection of human macrophages with S. enterica resulted in delayed apoptosis at about 18 to 24 h following infection and that the underlying reason was most likely the ADP-ribosylation of actin by SpvB (9). Strains harboring inactive SpvB do not induce apoptosis (9).…”
Section: Vol 76 2008 Actin Adp-ribosylation By C2 Toxin Delays Apopmentioning
confidence: 99%
“…Indeed, longterm residence and replication within phagocytic cells appear to be essential for Salmonella virulence because mutant bacteria that cannot survive or multiply inside macrophages are attenuated for systemic infection in mice (10). The complex nature of this hostpathogen interaction is further illustrated by recent evidence that Salmonella can kill macrophages via at least two distinct mechanisms, resulting in the rapid activation of host caspase-1 and caspase-2 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Caspase-1 is a member of a family of cysteinecontaining aspartate-specific proteases that play an important role in apoptosis (22,23).…”
mentioning
confidence: 99%